Peningkatan Literasi Dan Kepatuhan Pajak Melalui Pojok Pajak: Pendampingan Aktivasi Coretax Dan Pengisian Spt Tahunan Orang Pribadi - Amir, Asnidar; Faisalrahmat, Muh.; Qamariah, Nur; Yusuf, Irfan; Yusuf Y.S, Muhammad; Ismail Saleh, Muhammad; Irawati (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The digital transformation of tax administration through the Coretax Administration System (Coretax) requires taxpayers not only to understand tax regulations but also to possess the ability to utilize information technology effectively. As a newly implemented tax administration system for filing the 2025 Annual Individual Income Tax Return, (SPT Tahunana) Coretax still requires an adaptation process among taxpayers. Consequently, many taxpayers continue to encounter difficulties in activating their Coretax accounts, generating the Directorate General of Taxes (DJP) authorization code, and completing and submitting their Annual Individual Income Tax Returns. This community service program aimed to improve tax literacy and tax compliance through the Tax Corner (Pojok Pajak) program implemented at Universitas Sulawesi Barat in collaboration with the Tax Center and the Majene Primary Tax Office (KPP Pratama Majene). The program employed a participatory approach combined with direct assistance and was carried out in three stages: training prospective facilitators, assisting taxpayers with Coretax account activation, and providing guidance on the completion and submission of Annual Individual Income Tax Returns. The results demonstrated that the Tax Corner program improved participants' understanding of Coretax implementation, helped resolve various technical issues related to account activation and Annual Income Tax Return filing, and enhanced taxpayers' awareness and compliance in fulfilling their tax obligations. The program also demonstrates that collaboration between higher education institutions and the Directorate General of Taxes (DJP) is an effective strategy for supporting the digital transformation of tax administration while improving taxpayers' literacy and compliance.